Bioethanol carbon footprint: integrated 2019 report - Hilbert, Jorge Antonio (2019)
Report on bioethanol carbon footprint BIO4 BG1 BG2(2019). This document summarizes the preliminary analysis of the productive chain of bioethanol and by-products from corn by Bio4 and its integrated biogas plants Rio Cuarto Córdoba